2019
DOI: 10.1080/15548627.2019.1659608
|View full text |Cite
|
Sign up to set email alerts
|

De novo phosphatidylcholine synthesis is required for autophagosome membrane formation and maintenance during autophagy

Abstract: 2020) Denovo phosphatidylcholine synthesis is required for autophagosome membrane formation and maintenance during autophagy, ABSTRACT Macroautophagy/autophagy can enable cancer cells to withstand cellular stress and maintain bioenergetic homeostasis by sequestering cellular components into newly formed double-membrane vesicles destined for lysosomal degradation, potentially affecting the efficacy of anti-cancer treatments. Using 13 C-labeled choline and 13 C-magnetic resonance spectroscopy and western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 61 publications
4
60
1
Order By: Relevance
“…The present result clarified the physiological function of CCTβ3. This result differs from that of a recent study that concluded CCTα as the critical CCT isoform in autophagosome formation 38 . We argue that the prolonged loading of propargylcholine used for PC labeling in the study 38 (i.e., 6 vs. 1 h pulse loading in the present study) is not appropriate for visualizing de novo-synthesized PC because all cellular membranes including cargos engulfed by autophagosomes are intensely labeled by the protocol (see Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The present result clarified the physiological function of CCTβ3. This result differs from that of a recent study that concluded CCTα as the critical CCT isoform in autophagosome formation 38 . We argue that the prolonged loading of propargylcholine used for PC labeling in the study 38 (i.e., 6 vs. 1 h pulse loading in the present study) is not appropriate for visualizing de novo-synthesized PC because all cellular membranes including cargos engulfed by autophagosomes are intensely labeled by the protocol (see Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…1-oleoyl-2-palmitoyl-phosphatidylcholine (OPPC), an entity of phosphatidylcholine, is concentrated at the presynaptic area, playing a role in neuronal synapses in the brain 89 . On another level, by promoting de novo phosphatidylcholine synthesis, choline supplementation may affect the formation of autophagosomes 90 . Indeed, choline treatment normalized the levels of the autophagy markers towards those in the control group (Wt-Wt).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a lysosomal-mediated form of degradation in cells. The process of autophagy includes the formation of autophagosomes, autophagosome-lysosomal fusion, and autophagolysosomal degradation [12]. During degradation, an acidic pH and the enzymatic action of lysosomal hydrolase leads to destruction of the inner membrane of autophagosomes and the elimination of autophagolysosomes, thereby maintaining cell homeostasis [13].…”
Section: Introductionmentioning
confidence: 99%